An experimental comparison of different harvesting intensities with reduced-impact and conventional logging in East Kalimantan - Bertault, J.G.; Sist, P. (1997)
Timber harvesting was investigated both in terms of commercial timber volume extracted and impact on residual stand. Conventional (CNV) and reduced impact logging (RIL) techniques were compared on the basis of pre- and post-harvesting stand inventories. The timber volume extracted averaged 87 m3 ha-1 and the resulting commercial volume was 46 m3 ha-1 (i.e., 53.7% of the felled volume). On average, logging damage affected 40% of the residual trees (diameter at breast height (dbh) over 10 cm); injured and dead trees were recorded in equivalent proportions (21% and 19% respectively. Generally, felling operations caused injury to trees, crown damage being most common, whereas skidding caused death to trees, essentially by uprooting. Tree injury and death from RIL, in contrast, was substantially lower (30.5%) than from conventional methods (48.1%). This study demonstrated that the impact of logging on trees can be substantially reduced by strict supervision and planning of logging operations and limit of harvesting intensity, which should not exceed 80 m3 ha-1. If these technical recommendations are followed, it is possible to reduce the damage by 20%, which is equivalent to about 100 stems ha-1 (dbh over 10 cm).